Is Ace Inhibitor/Angiotensin-Receptor Blocker Associated with Acute Kidney Injury Post-Coronary Artery Bypass Grafting in a Mixed Ethnicity Population in a Community-Based Hospital in Hawai‘i? - Toledo, Ma Clarisse (University Clinical, Education & Research Associate (UCERA), 2013)
BACKGROUND: Acute kidney injury (AKI) after coronary artery bypass grafting (CABG) is common, and preoperative risk factors are well-established. Angiotensin-converting enzyme inhibitor/Angiotensin receptor blocker (ACEI/ARB) therapy has shown cardio-protective effects in coronary artery disease patients. However, there were concerns that preoperative use of ACEI/ARBs in cardiac surgery could cause extreme vasodilatation in the post-operative period thereby posing a risk to patients for the development of AKI post-surgery. The association between therapy with ACEI/ARB and acute kidney injury after cardiac surgery remains controversial. In this study, we aim to determine whether the preoperative use of ACEIs/ARB is associated with AKI post CABG in a mixed ethnicity population in Hawaii. METHODS: This was a retrospective study of 101 adult patients undergoing CABG between January 2009 and December 2011 in a single community-based hospital in Honolulu, Hawai‘i. Baseline data collection included patients' characteristics, peri-operative variables, and postoperative complications. The incidence of AKI was likewise obtained. Postoperative AKI was defined as an increase of 0.3 mg/dL or more in the serum creatinine from baseline in the first 48 hours after surgery. RESULTS: Of the 101 patients, AKI occurred in 34 patients (34%). The incidence of stage 1 and 2 AKI was 94% and 6%, respectively. There was no incidence of stage 3 AKI. Of all of the variables, only advanced age (≥ = 65 years old) (P = .0357)and preoperative cardiac catheterization (P = .0024) were significantly associated with an increased incidence of AKI. Otherwise, there was no significantly increased incidence of AKI with the following variables: gender (P = .3147), ethnicity (P = .4198), those who underwent both CABG and valve repair (P = .2611), insulin-dependent diabetes mellitus (P = .714),hypertension (P = .2539), hyperlipidemia (P =.805), COPD (P =.6011), preoperative use of ACEI/ARB (P =.6738), furosemide (P = .223), postoperative use of aspirin (P =.1598), and postoperative atrial fibrillation (P =.4367). Japanese accounted for the majority of the population (51%), followed by Filipino (18%), mixed ethnicity (8%), and others (23%). CONCLUSIONS: The incidence of AKI post CABG in this mixed ethnicity population in Hawai‘i is not different from other published studies. In addition, ACEI/ARB therapy is not associated with an increased risk of AKI post CABG, and our study suggests that preoperative discontinuation of ACEI/ARB may not be warranted.